2013
DOI: 10.2337/diaspect.26.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Association Among Depression, Physical Functioning, and Hearing and Vision Impairment in Adults With Diabetes

Abstract: Feature Article / Depression, Physical Functioning, and Sensory Impairment in Diabetes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 41 publications
(27 reference statements)
0
14
1
Order By: Relevance
“…It is noteworthy that these similar results come from two studies that used different measures of depression. Our finding on depression contradicts several other studies that found: no differences between DSL and single sensory impairment [35,36], worse results for DSL when compared to both VL and HL [38][39][40][41], and worse results for DSL only when compared to HL [37,42]. There are several differences between these prior studies and ours which may account for the mixed findings including diverse measures of sensory impairment and depression, and sample's age range.…”
Section: Discussioncontrasting
confidence: 99%
“…It is noteworthy that these similar results come from two studies that used different measures of depression. Our finding on depression contradicts several other studies that found: no differences between DSL and single sensory impairment [35,36], worse results for DSL when compared to both VL and HL [38][39][40][41], and worse results for DSL only when compared to HL [37,42]. There are several differences between these prior studies and ours which may account for the mixed findings including diverse measures of sensory impairment and depression, and sample's age range.…”
Section: Discussioncontrasting
confidence: 99%
“…Research indicates that depression contributes to suboptimal metabolic control (21), mediated in part by diabetes-specific emotional distress (10,22). Furthermore, the presence of depression in diabetes has been linked to advanced diabetes-related complications (23), greater functional impairment (24), more frequent intensive care unit admissions (25), and increased cardiac and all-cause mortality (2628). In turn, it is suggested that frequent hyperglycemia, the presence of diabetes complications, and comorbid conditions are associated with increased risk of depression (29).…”
Section: Introductionmentioning
confidence: 99%
“…Based on previous studies, the most common chronic illnesses among elderly include lung diseases (Kennison & Cox, 2013;Niti, Ng, Kua, Ho, & Tan, 2007;Manen et al, 2002); heart diseases (Kennison & Cox, 2013;Karakus & Patton, 2011;Clark & Currie, 2009); arthritis (Karakus & Patton, 2011;Niti et al, 2007); and diabetes (Karakus & Patton, 2011;Niti et al, 2007). Recent studies have dwelt on the impact of chronic illness on physical functioning (Loprinzi, Smit, & Pariser, 2013;Greenglass, Fiksenbaum, & Eaton, 2006;Nakajima et al, 2006;Manen et al, 2002;Kurtz, Kurtz, Stommel, Given, Given, 2001) and life satisfaction (Boen, Dalgard, Johansen, & Nord, 2012;Liyu & Guo, 2008). Notably, a negative correlation exists between chronic illness and the two aforementioned variables (Liyu & Guo, 2008).…”
Section: Chronic Illnessmentioning
confidence: 93%